IDENTIFIKASI PERMASALAHAN KAWASAN PESISIR PANTAI WAINITU KOTA AMBON - C. G. Buyang; Julius Buyang; Kathleen A Risakotta, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Wainitu Beach in Ambon City faces various environmental and infrastructure challenges that affect the quality of life of the community. I nfrastructure development that does not pay attention to environmental sustainability, domestic and industrial waste, are real threats to the sustainability of coastal ecosystems in this region. The purpose of the study is to identify problems in the coastal area of Wainitu Beach. The method used is qualitative which is descriptive to explain the existing phenomenon by providing a clear picture and in accordance with the facts in the field in detail as well as triangulation analysis. The main problem obtained is the limited infrastructure such as inadequate sanitation, drainage, and waste management systems, thereby increasing the risk of environmental pollution and damage to coastal ecosystems. The potential of marine tourism and fisheries at Wainitu Beach is still not optimally worked on due to the lack of supporting infrastructure and immature planning. Other issues such as limited accessibility, and lack of maintenance and maintenance of existing infrastructure also point to the need for more structured interventions and development. Therefore, it is necessary to improve infrastructure, sustainable management of natural resources, and the active participation of all stakeholders.